The impact of HIV exposure status and maternal feeding practice on the concentration of SLPI and E/tr-2 protein in infant saliva and maternal breast milk - Dontsa, Nobomi (Department of Clinical Laboratory Sciences, 2023)
Background Among infants, postnatal HIV transmission occurs via the oral route when ingesting breastmilk containing HI-virions (Kuhn et al., 2007). HIV acquisition via this route is however very low, possibly due to the presence of innate proteins in the oral secretions. Such innate proteins with anti-HIV activity include secretory leukocyte protease inhibitors (SLPI) and Elafin/trappin-2 (E/tr-2). At physiological concentrations SLPI and E/tr-2 have been shown to inhibit in vitro HIV replication in human monocytes and epithelial cells, respectively. Study Aims 1) To determine the impact of HIV infection/ exposure on the concentration of SLPI and E/tr-2 in maternal breast milk and infant saliva; 2) To investigate the impact of of feeding modes on the concentration of innate proteins in infant saliva. Methods This study compared the concentrations of SLPI and E-tr2 among three groups of maternal-infant pairs to address the study aims. Saliva was collected from HIV unexposed breast fed (UBF, n=135), HIV exposed breastfed (EBF, n=151) and HIV exposed formula fed (EFF, n=141) infants together with breast milk from HIV negative (HIV-ve, n=144) and HIV positive (HIV+ve, n=165) mothers. SLPI and E/tr-2 concentrations were measured in samples collected at birth, 15 and 36 weeks of infant age using ELISA. Results Breast milk concentrations of SLPI and E/tr-2 significantly decreased over time in both HIV+ve and HIV-ve women. The salivary SLPI concentration in HEU infants significantly increased over time. In the HU infants, significantly high SLPI concentrations were observed at birth, however the concentration of the analyte was significantly decreased at week 15 and then increased again significantly at week 36. The concentration of E/tr-2 in infant saliva remained the same at all-time points. No significant differences were observed in breast milk SLPI and E/tr-2 concentrations between HIV+ve and HIV-ve mothers at birth and 15 weeks of infant age. However, breast milk SLPI concentrations were significantly higher in the HIV-ve mothers compared to the HIV+ve mothers at 36 week of infant age. Salivary SLPI concentrations were significantly higher in the HU infants at birth, however, at 15 weeks of age an inverse was observed where HEU infants had significantly high SLPI concentrations compared to the HU infants. Additionally, salivary SLPI concentration was significantly higher in HIV exposed formula fed infants compared to HIV exposed breast fed infants at birth. However these differences dissipated with advancing age. No differences were observed for E/tr-2 concentration for both breast fed and formula fed infants. Lastly, no correlation was observed between maternal breast milk and infant salivary SLPI and E/tr-2 concentration at all-time points. Discussion The production of SLPI and E/tr-2 in infants is possibly due to inflammation as a results of bacterial LPS or other factors and not breastfeeding as originally hypothesized. In our cohort, we observed that elevated or low concentrations of SLPI in maternal breast milk is independent of HIV infection. However, in infant saliva HIV exposure played a significant role. An interesting finding in our study was that infants who received breast milk at birth had significantly low SLPI concentrations compared to those who were exclusively formula fed. However, at 15 and 36 weeks of infant age the concentration of SLPI increased probably due to ongoing exposure. It was also notable that we did not see any changes in E/tr-2 concentrations over time nor differences at all time points. Conclusion The data suggest that HEU infants produce sufficient SLPI concentrations capable of blocking HIV infection at 15 weeks of life, as previously shown (Mcneely et al., 1995, Bacqui et al., 2002). Further studies are required to investigate the ability of this protein to block HIV infection in vitro using human saliva.